A Coreflood‐on‐a‐Chip Study of Viscoelasticity's Effect on Reducing Residual Saturation in Porous Media. Issue 8 (6th August 2021) - Du, Yujing; Xu, Ke; Mejia, Lucas; Balhoff, Matthew
Abstract: Polymer aqueous solutions are widely used in nonaqueous phase liquid recovery and aquifer remediation processes due to their high viscosity. Additional reduction of residual saturation by polymer's viscoelasticity has recently been discovered which elevates the ultimate displacement efficiency. However, there is no consensus on how, and under what conditions, viscoelasticity reduces residual saturation. This is in part because most studies utilize relatively low salinity and high viscosity, which also contribute to higher recoveries. We separate the effects of viscosity, elasticity and salinity, by performing microfluidic experiments in long (30 cm) heterogeneous glass micromodels ( coreflood‐on‐a‐chip ). In the experiments, a highly viscous Newtonian aqueous phase flood is first performed so that the system reaches residual saturation, followed by polymer flood with varying elasticity and salinity. This is followed by another highly viscous Newtonian aqueous phase flood. We observe significant redistribution and reconnection of residual ganglia due to viscoelasticity induced instabilities during high‐viscoelasticity polymer floods, which results in residual ganglia remobilization that ultimately reduces residual saturation. In contrast, no fluid redistribution and saturation reduction are observed in low‐viscoelasticity polymer floods. During low salinity polymer floods (regardless of the relative elasticity), spontaneous emulsification occurs inside ganglia and results in ganglia swelling, which enhances ganglia reconnection when elastic instability happens, therefore amplifies the residual saturation reduction. Key Points: Viscoelasticity helps in reducing the residual fluid saturation without posing extraordinal large viscous force The residual saturation reduction attributes to viscoelastic instabilities induced reconnection and redistribution of residual ganglia Low salinity enhances the residual fluid reconnection and redistribution by swelling residual ganglia when elasticity is high